The effect of passive leadership on behavioral incivility and workplace incivility of employees in Indonesia public organizations - Tunggul Prasodjo (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The purpose of this study was to analyze the relationship between Passive Leadership variables and Behavioral Incivility, the relationship between Passive Leadership variables and Workplace Incivility and the relationship between Workplace Incivility variables and Behavioral Incivility in Indonesia public organizations. This research belongs to the type of descriptive quantitative research, namely research that aims to explain and explain descriptive information. The subjects taken in this study were 210 employee in Indonesia public organizations during the COVID-19 pandemic which were determined by the random sampling system method. Data was obtained by distributing online questionnaires with a Likert scale of 1 to 7 through social media. The analysis technique used Structural Equation Modeling (SEM) with data processing tools SmartPLS 3.0 software. The independent variable in this study is Passive Leadership, while the dependent variables are Behavioral Incivility and Workplace Incivility. The increase in the passive leadership variable does not have a significant effect on the behavioral incivility variable. There is a significant effect of passive leadership on workplace incivility in Indonesia public organizations. There is a significant influence between workplace incivility on behavioral inclusivity in Indonesia public organizations.